Endovascular Treatment of Large or Giant Basilar Artery Aneurysms Using the Pipeline Embolization Device: Complications and Outcomes - Ge, Huijian; Chen, Xiheng; Liu, Kai; Zhao, Yang; Zhang, Longhui; Liu, Peng; Jiang, Yuhua; He, Hongwei; Lv, Ming; Li, Youxiang (Frontiers in Neurology, 2022)
Background: This study aimed to investigate clinical and angiographic outcomes of Pipeline embolization device (PED) treatment of large and giant basilar artery (BA) aneurysms and examine associated factors. Methods: Clinical and angiographic data of 29 patients (18 men, 11 women) with large or giant BA aneurysms were retrospectively examined. Mean age was 44.1 ± 21.2 years (range, 30–68). Mean aneurysm size was 22.2 ± 8.3 mm (range, 12.0–40.1). Results: Mean angiographic follow-up was 18.3 ± 3.4 months (range, 4.5–60). The rate of adequate aneurysmal occlusion (O’Kelly–Marotta grade C–D) was 87%. The overall complication rate was 44.8%; most complications (84.6%) occurred in the periprocedural period. Univariable comparison of patients who did and did not develop complications showed significant differences in aneurysm size (p <0.01), intra-aneurysmal thrombus (p = 0.03), and mean number of PEDs used (p = 0.02). Aneurysm size (odds ratio, 1.4; p = 0.04) was an independent risk factor for periprocedural complications in multivariable analysis. Mean clinical follow-up was 23.5 ± 3.2 months (range, 0.1–65). Nine patients (31%) had a poor clinical outcome (modified Rankin scale score ≥3) at last follow-up, including 7 patients who died. Univariable comparisons between patients with favorable and unfavorable clinical outcomes showed that aneurysm size (p = 0.009) and intra-aneurysmal thrombus (p = 0.04) significantly differed between the groups. Multivariable analysis showed that aneurysm size (odds ratio, 1.1; p = 0.04) was an independent risk factor for poor clinical outcome. Conclusion: PED treatment of large and giant BA aneurysms is effective and can achieve a satisfactory long-term occlusion rate. However, the treatment complications are not negligible. Aneurysm size is the strongest predictor of perioperative complications and poor clinical outcome.